THE GREAT MOVE TOWARDS OPENNESS IN ADOPTION (The Pretoria Student Law Review, 2021)
Many noteworthy changes have occurred in South African adoption law in the recent past: With the enactment of the Children’s Act, various new concepts have been provided for. A post-adoption agreement is one such concept. This provision allows the Children’s Court to grant an order confirming an agreement whereby the biological parent/s or guardian/s of a child would have the benefit of either communication or contact with the adopted child, or the right to be provided with certain information concerning such child. An application for judicial approval of a post-adoption agreement is brought before the court simultaneously alongside the adoption order. This is a major step towards the concept widely known in the international community as ‘openness’ in the adoption process, and away from the secrecy which dominated adoptions in the past. Currently in South Africa, adoption may be described as an ‘... order [which] has the effect of creating a legal relationship between the adoptive parent and the adopted child in the interests of the child.’ This involves the severing of legal ties between the birth parents and their child, relinquishing all parental rights and responsibilities and handing them over to the adoptive parents. Therefore in the eyes of the law, the adopted child is, for all purposes, the child of the adoptive parent/s. Due to the fact that this is the first time the South African legislature has sought to provide for and regulate post-adoption contact, this article serves as an exploration into the new possibilities and struggles South Africa may face in this regard.
Keywords: South Africa; adoption law; Children’s Act; post-adoption agreement; ‘openness’; relinquishing all parental rights and responsibilities; child of adoptive parent/s